2020
DOI: 10.1002/psp.2354
|View full text |Cite
|
Sign up to set email alerts
|

Young adults' return migration from large cities in Sweden: The role of siblings and parents

Abstract: Living in cities affects young adults' access to education and work. With the use of register data for 2000-2013, we examined the role of having siblings and parents living close by and having siblings and parents living in the area of origin, in young adults' return migration from the four largest cities in Sweden. We found that young adults were less likely to return, and also less likely to migrate elsewhere, if they had siblings or parents living in the city of residence than if this was not the case. If t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…Fischer and Malmberg 2001). As such, the "magnetizing effect" of family serves as an attraction for individuals to remain in an area or move elsewhere (Mulder and Gillespie 2021), including returns to one's birth region after moving away or toward other places close to family (e.g., Gillespie, Mulder, and von Reichert 2021;Hedman 2013;Mulder, Lundholm, and Malmberg 2020;Spring et al 2017).…”
Section: The Role Of Nearby Family and Friends In Residential Mobilitymentioning
confidence: 99%
“…Fischer and Malmberg 2001). As such, the "magnetizing effect" of family serves as an attraction for individuals to remain in an area or move elsewhere (Mulder and Gillespie 2021), including returns to one's birth region after moving away or toward other places close to family (e.g., Gillespie, Mulder, and von Reichert 2021;Hedman 2013;Mulder, Lundholm, and Malmberg 2020;Spring et al 2017).…”
Section: The Role Of Nearby Family and Friends In Residential Mobilitymentioning
confidence: 99%
“…However, research on the role of siblings in internal migration lags behind a growing number of studies on the role of adult children as the motive for migration. Some noteworthy exceptions to this trend have recently focused on the role of siblings in the migration choices of young adults ( Mulder et al, 2020a , 2020b ). Additionally, existing studies about family proximity-enhancing moves, also known as geographic convergence ( Silverstein, 1995 ), often ignore older adults who do not have children.…”
mentioning
confidence: 99%
“…First and foremost, return migrants listed their parents as the focal point of the return to move (Mulder & Lundholm, 2020). This is supported by Hussain et al (2017), where family reason was indicated as the main motivation in returning to the rural areas due to responsibility factor.…”
Section: Following Familymentioning
confidence: 83%
“…Reverse migration can be caused by difficult conditions such as poor salaries, or unemployment (Mulder & Lundholm, 2020). All commercial businesses have closed their operations due to the nationwide lockdown, resulting in unemployment and people returning to their hometowns or villages (Chakma, 2020).…”
Section: Career/occupationmentioning
confidence: 99%
See 1 more Smart Citation